1998
DOI: 10.1007/s001250050987
|View full text |Cite
|
Sign up to set email alerts
|

Short stature in Korean women: a contribution to the multifactorial predisposition to gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM), which is defined as carbohydrate intolerance of variable severity with onset or first recognition during the present pregnancy [1], is associated with adverse outcomes of pregnancy including macrosomia, birth trauma and metabolic complications of the newborn [2±4]. Although most women with GDM have a normal glucose tolerance when tested several weeks postpartum, impairment of insulin secretory capacity or increased insulin resistance or both have been reported in these wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 26 publications
10
94
1
1
Order By: Relevance
“…Although publication bias cannot be ruled out, the challenge in including short stature as a risk factor for gestational diabetes mellitus seems to be the definition of the cut-off point for this variable. In Brazil, based on the Brazilian Gestational Diabetes Study (EBDG), the study of Branchtein et al 27 defined it as ≤ 151cm, however studies in other countries observed associations using different height categories 21,25,26,29,33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although publication bias cannot be ruled out, the challenge in including short stature as a risk factor for gestational diabetes mellitus seems to be the definition of the cut-off point for this variable. In Brazil, based on the Brazilian Gestational Diabetes Study (EBDG), the study of Branchtein et al 27 defined it as ≤ 151cm, however studies in other countries observed associations using different height categories 21,25,26,29,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al 25 1998 and Di Cianni et al 33 2003 found greater ratio of women with gestational diabetes mellitus in the group with parity ≥ 2, in comparison to primiparas. After controlling for age, pre-pregnancy BMI, height, family history of diabetes mellitus and weight gain during pregnancy, both results were non statistically significant.…”
Section: Paritymentioning
confidence: 97%
See 2 more Smart Citations
“…Unfortunately, two authors could not provide the requested information, so these studies could not be included in the meta-analysis [20,21]. If papers reported associations between GWG and GDM but did not use IOM criteria for GWG, then the authors were contacted and asked to rerun their analysis [16,17,[22][23][24][25][26][27][28][29][30][31]. Additional analyses were provided by two authors [17,22].…”
Section: Study Selectionmentioning
confidence: 99%